1988
DOI: 10.1136/ard.47.12.972
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of anaemia in rheumatoid arthritis: demonstration of raised interleukin 1 beta concentrations in anaemic patients and of interleukin 1 mediated suppression of normal erythropoiesis and proliferation of human erythroleukaemia (HEL) cells in vitro.

Abstract: SUMMARY The pathogenesis of the anaemia associated with rheumatoid disease is unclear. It has previously been shown that the degree of the anaemia correlates with the severity of the inflammatory disease and that serum from patients with arthritis inhibits erythropoiesis. This study was designed to examine whether interleukin 1 could be a mediator of the anaemia in rheumatoid arthritis. Radioimmunoassay of interleukin 1 in serum showed that patients with rheumatoid arthritis and associated anaemia had signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1
6

Year Published

1993
1993
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(49 citation statements)
references
References 52 publications
3
39
1
6
Order By: Relevance
“…35,36 Individual cytokines, such as IL-6, have also been correlated with the severity of the anemia in chronic disease states. [37][38][39] Colony-forming assays are robust assays of proliferative capacity, but they are not well suited for the analysis of the later stages of erythroid maturation. Late stages of erythroid maturation proceed independently of erythropoietin and after the majority of cell divisions have occurred.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Individual cytokines, such as IL-6, have also been correlated with the severity of the anemia in chronic disease states. [37][38][39] Colony-forming assays are robust assays of proliferative capacity, but they are not well suited for the analysis of the later stages of erythroid maturation. Late stages of erythroid maturation proceed independently of erythropoietin and after the majority of cell divisions have occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the addition of anti-IL-6 antibody did not ablate the IL-1 effect. IL-1 induces hypoferremia (17), up-regulates ferritin (18), and has been thought to play a primary role in the anemia of chronic inf lammation (8). It may well be that it is stimulation of hepcidin by IL-1 that plays a more important role in the anemia of inf lammation than does IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…17 Johnson et al 18 exposed mice to a single intravenous dose of TNF-a,which resulted in suppression of spleen and marrow erythroid colony-forming units. Johnson et al 18 treated mice with single or repeated intraperitoneal injections of recombinant human IL-1a, which resulted in suppression of mature erythroid progenitors within 6 hours.Maury et al 19 reported that recombinant human IL-1 (a and b) inhibited in vitro colony formation by erythroid burst-forming units and erythroid colony forming units from normal human marrow. In vitro colony formation by marrow granulocyte-macrophage progenitors was not inhibited by IL-1a.…”
Section: Means Of the Hematocrit Values In The Three Groupsmentioning
confidence: 99%